AMMONIUM AS A BIOMARKER IN PRECAMBRIAN METASEDIMENTS - Boyd S.R. (My University, 2001)
The following article assesses the potential of ammonium as a biomarker in Precambrian metasediments. A modern marine environment is considered to highlight the processes that contribute to the isotopic composition of organic nitrogen, notably the roles played by nitrogen-fixing organisms (cyanobacteria) and denitrifying bacteria. The carbon and nitrogen biogeochemical cycles are compared and contrasted. Unlike carbon, the major nitrogen isotope variations may be controlled by local environmental conditions, such as season of the year and water depth. However, such local environmental factors may have been superimposed on more gradual changes related to the long-term chemical evolution of the exterior environments of the Earth. The great potential of nitrogen as a biomarker is that the breakdown product of organic nitrogen (ammonium) behaves like a trace element, and is stable in high temperature crustal processes. Thus, ammonium may survive as a biomarker when all other evidence for former life has been destroyed, and ammonium studies may be able to identify sedimentary (pelitic) components in high-grade Precambrian terrains. Previous results from Precambrian rocks are reviewed, to highlight that very little work has been completed to date, and that only very general conclusions can be drawn. Much work needs to done in order to understand the basic biogeochemistry and geochemistry of crustal nitrogen, and it is suggested that the best way to proceed is by numerous detailed case studies. The interpretation of isotope ratios in ancient sediments usually assumes uniformitarianism, and the justification of this approach is considered briefly. Overall, this article highlights the under-developed potential of Precambrian ammonium biogeochemistry, and suggests area for future research. Not only does the development of the subject have implications for the search for former life on Mars, but it may also open up new areas of Precambrian research.
Keywords: NITROGEN CYCLE; NITROGEN ISOTOPES; BIOGEOCHEMISTRY; SEDIMENTS; CONTINENTAL CRUST